Communication and satisfaction with the consultation in general practice: A prospective examination - Iconomou, Gregoris; R. Rutter, Derek (Psychology: the Journal of the Hellenic Psychological Society, 2020)
ABSTRACT IS AVAILABLE IN THE PDF